Anthropometry and performance of top youth international male basketball players in Spanish national academy - Gonzalez, J. C.; Ayuso, J. M.; Lekue, J. A.; Leibar, X.; Erauzkin, J.; Jukic, I.; Ostojic, S. M.; Ponce González, J. G.; Azpiroz, M. F.; Terrados, N. (Nutrición Hospitalaria, 2018)
The "Century XXI" Project is a seven-year intervention sport program performed among the best Spanish youth basketball players, who were assigned to one of the following intervention groups based on the following criteria: age, position, mature level, and origin in the country. The study was performed (1996-2001) with a total of 90 players. The main purposes of this study were: a) to describe anthropometric and performance characteristics of top youth international male basketballers in the Spanish national academy; and b) to analyze differences among positions. Insummary, the main findings of this study were: a) the anthropometry presented significant differences between groups under (U-) 14 and U-17; and b) in the U-17 group centers presented more arm span. In our study, the most significant changes are in U-16 vs U-14 and U-15 in strength body up values, and the best result in endurance capacity took place in June of the fourth year. Within this context, the results of the present study may be useful for strength and conditioning coaches to plan their programs with youth basketball players.